Strategi Peningkatan Perilaku Kerja Inovatif Berbasis Kepemimpinan: Peran Mediasi Moderasi Knowledge Sharing dan Creative Self-Efficacy - Nurali, Nurali; Kurniawan, Indra; Hidayati, Nurul (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study analyzes the influence of transformational leadership on innovative work behavior through knowledge sharing, which acts as a mediator, and creative self-efficacy as a moderator. A quantitative approach was used with a cross-sectional design and survey method. A total of 301 data were collected through questionnaires distributed to lecturers at Private Universities (PTS) in East Java. The data were analyzed using the SEM method with SmartPLS 4.0. The results of the analysis obtained a direct effect of transformational leadership on innovative work behavior. Further findings show that knowledge sharing partially mediates the effect of transformational leadership on innovative work behavior. Creative self-efficacy was also shown to strengthen the influence of transformational leadership and knowledge sharing on innovative work behavior. These findings indicate that the higher an individual's belief in their creative abilities, the stronger the influence of transformational leadership and knowledge sharing in improving innovative work behavior.